Usage of Colloquial-Dialectical Vocabulary in Modern Armenian Advertising Speech - Sargsyan, Liana (Bulletin of Yerevan University B: Philology, 2023)
The following article argues the application of colloquial-dialectal units in advertising speech. Cases that are acceptable in terms of marketing and advertising speech targeting are discussed separately. They are such moderate usages that are directly connected to people’s simple speech and mindset, making advertisements memorable and impressive. In the Republic of Armenia (RA), the advertising agency and the advertiser oftentimes prefer the application of these language units. The choice of the topic and the determination of the target audience, the addressee, dictate certain word choice and word combinations principles, which should also contribute to the formation of concise speech. And often topic, to ensure a direct connection between the subject and the addressee, the compression of the speech is formed by the choice of a well-known motive and the "everyday vocabulary" adapted to it. In order to talk to the public more easily, and to orientate in a language that is universally understandable and close to the people, linguistic means are sought from the vernacular itself. AIDA advertising model is justified even in the sense of some samples that are presented in the discussion that violate the law on advertising and form low taste perceptions in society. There are also recommendations for structuring and developing the advertisement text.